Filtering Brackish Water by Photovoltaic-Powered Membrane - Wei Guo, Kelvii; Yuen Tam, Hon (Journal of Membrane and Separation Technology, 2016)
Photovoltaic-powered membrane was taken to filter brackish water. Effect of ammonia concentration, pressure and salinity on ammonia and total dissolved solids (TDS) removal, water recovery and energy consumption had been investigated. Results show that ammonia concentration did not influence ammonia and TDS removal, water recovery, and energy consumption obviously. Results of ammonia concentration of 10, 20 and 35 mg/l were similar to that of 5 mg/l. For salinity, the better filtration was achieved when the concentration of salinity was lower. With increment of pressure, ammonia and TDS removal increased simultaneously. The ammonia and TDS removal of more than 98% attained with the water recovery of 40.6% at the energy consumption of 2.0 kWh/m3. It illustrates that salinity and pressure were definitely crucial to brackish water filtration with photovoltaic-powered membrane.